How Black Swan events reveal known and unknown unknowns : the case of COVID-19 - Beßlich, Sina (2020)
The unknown offers a great puzzle to strategists. Black Swan events, characterized by rare occurrence and retrospective predictability, have extreme impacts on economies and societies (Taleb, 2007). The primary research purpose of this study is to examine whether Black Swan events increase awareness of known and unknown unknowns by discovering perceptions of existing and novel uncertainties. Precisely, we analyze how unexpected tail events enhance consciousness of unknown unknows and alter mental models of known uncertainties. To discover a recent Black Swan phenomenon, we chose the novel Coronavirus (COVID-19) as empirical context. Qualitative examination of 36 semi-structured interviews implies that the Coronavirus crisis considerably changes the range of uncertainties, which can shape future management research and practice. Although the majority of discovered uncertainty areas (72.5%) were recognized ex ante COVID-19, our findings show that the current pandemic also reveals strategically relevant unknown unknowns. Based on the framework of environmental uncertainty developed by Jauch and Kraft (1986), we develop a novel model that illustrates strategic decision-making in the context of Black Swan uncertainties. 2020’s Black Swan, COVID-19, triggers strategic decision-makers to reconsider current interdependencies to reduce the potential harm of future uncertainty shocks. Since our results disclose that uncertainty related to Black Swan events essentially creates novel uncertainties, executives are required to acknowledge that they cannot ignore or eliminate uncertainty. Instead, managers are advised to embrace the occurrence of Black Swans and the existence of known and unknown unknowns for (anti)knowledge exploration.